Late Miocene submarine volcanism in ANDRILL AND-1B drill core, Ross Embayment, Antarctica - Massimo Pompilio; Alessio Di Roberto; T. I. Wilch (Geosphere, 2010)
The ANDRILL McMurdo Ice Shelf initiative recovered a 1285-m-long core (AND-1B) composed of cyclic glacimarine sediments with interbedded volcanic deposits. The thickest continuous volcanic sequence by far is ∼175 m long and is found at mid-core depths from 584.19 to 759.32 m below seafloor. The sequence was logged, and initial interpretations of lithostratigraphic subdivisions were made on ice during drilling in late 2006. Subsequent observations, based on image, petrographic, and scanning electron microscopy–energy dispersive spectroscopy analyses, provide a more detailed, revised interpretation of a thick submarine to emergent volcanic succession. The sequence is subdivided into two main subsequences on the basis of sediment composition, texture, and alteration style. The ∼70-m-thick lower subsequence consists mostly of monothematic stacked volcanic-rich mudstone and sandstone deposits, which are attributed to epiclastic gravity flow turbidite processes. This subsequence is consistent with abundant active volcanism that occurred at a distal site with respect to the drill site. The ∼105-m-thick upper subsequence consists mainly of interbedded tuff, lapilli tuff, and volcanic diamictite. A Late Miocene (6.48 Ma) 2.81-m-thick subaqueously emplaced lava flow occurs within the second subsequence. This second subsequence is attributed to recurring cycles of submarine to emergent volcanic activity that occurred proximal to the drill site. This new data set provides (1) the first rock evidence of significant Late Miocene submarine volcanic activity in the Ross Embayment during a period of no to limited glaciation, and (2) a rich stratigraphic record that elucidates submarine volcano-sedimentary processes in an offshore setting.